Twenty questions and answers about the ozone layer (World Meteorological Organization GenevaCH, 2011)
This publication is a component of the 2010 report of the Montreal Protocol Scientific Assessment Panel, Scientific Assessment of Ozone Depletion: 2010. The answers are based on the information presented in the Assessment report in June 2010.
Keywords: OZONE